Peran Kepemimpinan Kepala Madrasah dalam Meningkatkan Kreativitas Guru di MI Andzariyah Batuputih Sumenep - Zahrotul Jannah; Ashari Ashari (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2024)
The results showed that the role of the madrasah head in MI Andzariyah Batuputih Sumenep has a significant impact on increasing teacher creativity. The madrasah head has made efforts to create an environment that supports creativity through training, providing resources, guidance and creating a conducive environment. The training attended by teachers has shown an increase in creativity and courage in experimenting with new learning techniques. However, although resources such as technology have been provided, most teachers still use conventional learning methods, suggesting that the madrasah head's encouragement has not been fully implemented. Other challenges include resistance to change, lack of motivation and limited technology skills among teachers. The madrasah principal's support is only felt by teachers who are motivated and ready to follow directions, indicating the importance of teachers' own self-motivation. Nevertheless, the positive impact of the madrasah principal's role is seen in the increased motivation and enthusiasm of more creative teachers, which in turn will improve the quality of learning and learner outcomes. Therefore, it is necessary to increase the motivation and readiness of teachers to take advantage of the support provided, so that learning in madrasah can become more creative, interactive and quality.